Facile Formation of Nanodisk‐Shaped Orthorhombic SnS Layers from SnS2 Particles for Photoelectrocatalytic Hydrogen Production. Issue 8 (10th July 2017) - Patel, Malkeshkumar; Yu, Xiaomei; Kim, Yu Kwon; Kim, Joondong
Abstract: SnS has a great potential for use as a photocatalyst for the production of chemical fuels out of sunlight. For the use of it as a photocatalyst, a fast and reliable method of fabricating pure layered crystalline SnS is required. Here, we present a simple and efficient method of fabricating high‐quality SnS layers as a thin film on various substrates such as Si, quartz, glass and FTO. The nanodisk‐shaped p‐type SnS films are obtained starting from SnS2 via a one‐step process involving phase dissociation and sulfur reduction. The prepared SnS films show interesting thickness‐dependent physical properties such as optical band gap, absorption coefficient and flat band potential, which suggest the possibility of tuning its property by controlling the thickness. Especially, the SnS films with the thickness of 20 nm or less show an enhanced absorption above the band gap and an increased free carrier concentration. With such advantageous photoresponsive properties, we observed a good hydrogen production activity (order of 100 μmol h −1  cm −2 ) from the thin SnS films under photoelectrocatalytic reaction conditions. The measured efficiency in hydrogen evolution is explained from a favorable band alignment as well as the good photoresponse of the film. Combined with the facile fabrication of high‐quality thin SnS films, our analysis shows that nanodisk‐shaped SnS is a promising material for a future development of photocatalytic production of hydrogen as a chemical fuel. Abstract : Orthorhombic SnS with an analogous structure as black phosphorus, yet with a finite band gap unlike graphene, has gained attention among two‐dimensional materials. A one‐pot‐fabricated, high‐quality, SnS nanodisk film with thickness 20 nm or less showed enhanced absorption above the band gap, increased carrier concentration, and photoelectrocatalytic hydrogen production on the order of 100 μmol h −1  cm −2 .